What is this matrix doing?

Algebra Level 4

Consider the matrix equation:

( 1 1 0 0 1 1 1 0 1 ) ( 2 1 + a 2 1 + a ) = ( A B C ) \begin{pmatrix} 1 & -1 & 0 \\ 0 & 1 & -1 \\ -1 & 0 & 1 \end{pmatrix} \begin{pmatrix} 2 \\ 1 + a^2 \\ 1+a \end{pmatrix} = \begin{pmatrix} A \\ B \\ C \end{pmatrix}

In the above equation, a = e j 2 π / 3 a = e^{j 2 \pi /3} and j = 1 j = \sqrt{-1} .

Determine the following quantity.

A + B + C + A + B + C |A + B + C| + |A| + |B| + |C|

Hint: Superposition is a helpful concept here


The answer is 5.196.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 11, 2019

[ A B C ] = [ 1 1 0 0 1 1 1 0 1 ] [ 2 1 + a 2 1 + a ] = [ 1 1 0 0 1 1 1 0 1 ] [ 1 1 1 ] + [ 1 1 0 0 1 1 1 0 1 ] [ 1 a 2 a ] = [ 0 0 0 ] + [ 1 a 2 a 2 a a 1 ] = ( a 1 ) [ a 2 a 1 ] \begin{aligned} \begin{bmatrix} A \\ B \\ C \end{bmatrix} & = \begin{bmatrix} 1 & -1 & 0 \\ 0 & 1 & -1 \\ -1 & 0 & 1 \end{bmatrix} \begin{bmatrix} 2 \\ 1+a^2 \\ 1+a \end{bmatrix} \\ & = \begin{bmatrix} 1 & -1 & 0 \\ 0 & 1 & -1 \\ -1 & 0 & 1 \end{bmatrix} \begin{bmatrix} 1 \\ 1 \\ 1 \end{bmatrix} + \begin{bmatrix} 1 & -1 & 0 \\ 0 & 1 & -1 \\ -1 & 0 & 1 \end{bmatrix} \begin{bmatrix} 1 \\ a^2 \\ a \end{bmatrix} \\ & = \begin{bmatrix} 0 \\ 0 \\ 0 \end{bmatrix} + \begin{bmatrix} 1 - a^2 \\ a^2 - a \\ a - 1 \end{bmatrix} \\ & = (a-1)\begin{bmatrix} a^2 \\ a \\ 1 \end{bmatrix} \end{aligned}

Therefore,

X = A + B + C + A + B + C = ( a 1 ) ( a 2 + a + 1 ) + ( a 1 ) a 2 + ( a 1 ) a + ( a 1 ) Note that a 2 + a + 1 = 0 = 0 + a 1 ( a 2 + a + 1 ) and a 2 = a = 1 = 3 e 2 3 π i 1 = 3 1 2 + 3 2 i 1 = 3 3 2 + 3 2 i Euler’s formula: e θ i = cos θ + i sin θ = 3 9 4 + 3 4 = 3 3 5.196 \begin{aligned} X & = |A+B+C| + |A|+|B|+|C| \\ & = |(a-1){\color{#3D99F6}(a^2+a+1)}| + |(a-1)a^2| + |(a-1)a| + |(a-1)| & \small \color{#3D99F6} \text{Note that }a^2 + a + 1 = 0 \\ & = 0 + |a-1|\color{#3D99F6} (|a^2|+|a|+1) & \small \color{#3D99F6} \text{and }|a^2| = |a| = 1 \\ & = 3 \left|{\color{#3D99F6}e^{\frac 23\pi i}} - 1\right| = 3 \left|{\color{#3D99F6}-\frac 12 + \frac {\sqrt 3}2 i} - 1\right| = 3 \left|-\frac 32 + \frac {\sqrt 3}2 i \right| & \small \color{#3D99F6} \text{Euler's formula: }e^{\theta i} = \cos \theta + i\sin \theta \\ & = 3\sqrt{\frac 94+\frac 34} = 3\sqrt 3 \approx \boxed{5.196} \end{aligned}

Tom Engelsman
Sep 11, 2019

After performing the matrix multiplication out, one obtains:

A = 1 a 2 = 1 e j 4 π / 3 = 3 2 + 3 2 j A = 1 - a^2 = 1 - e^{j4\pi / 3} = \frac{3}{2} + \frac{\sqrt{3}}{2}j ;

B = a 2 a = e j 4 π / 3 e j 2 π / 3 = 3 j ; B = a^2 - a = e^{j4\pi / 3} - e^{j2\pi / 3} = -\sqrt{3}j;

C = a 1 = e j 2 π / 3 1 = 3 2 + 3 2 j C = a - 1 = e^{j2\pi /3} - 1 = -\frac{3}{2} + \frac{\sqrt{3}}{2}j

and the following magnitudes:

A + B + C = 0 , A = C = ( 3 / 2 ) 2 + ( 3 / 2 ) 2 = 3 , B = 3 |A+B+C| = 0, |A| = |C| = \sqrt{(3/2)^2 + (\sqrt{3} / 2)^2} = \sqrt{3}, |B| = \sqrt{3}

and the final sum:

A + B + C + A + B + C = 3 3 . |A+B+C| + |A| + |B| + |C| = \boxed{3\sqrt{3}}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...